2021
DOI: 10.1002/cncr.33676
|View full text |Cite
|
Sign up to set email alerts
|

The PREPARE for Your Care program increases advance care planning engagement among diverse older adults with cancer

Abstract: Background Advance care planning (ACP) is low among older adults with cancer. In a secondary analysis of randomized trial data, the authors compared the efficacy of the PREPARE for Your Care (PREPARE) website plus an easy‐to‐read advance directive (AD) with an AD only among older adults with and without cancer. Methods Safety net, primary care patients in San Francisco were included if they were 55 years old or older, were English‐ or Spanish‐speaking, and had 2 or more chronic conditions. The authors determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The PREPARE for Your Care tool, used in 15 studies, innovatively incorporated a hybrid delivery method, offering adaptability across varying patient needs. 13 27 Conversely, tools such as PROVEN 28 33 and Hello Project 34 38 used video and game-based approaches respectively, illustrating the variety of delivery methods. The web-based tool, Making Your Wishes Known, 39 43 offers wide accessibility, while PC-ACP 44 48 and SPIRIT 49 53 highlight the significance of individual counseling in ACP.…”
Section: Resultsmentioning
confidence: 99%
“…The PREPARE for Your Care tool, used in 15 studies, innovatively incorporated a hybrid delivery method, offering adaptability across varying patient needs. 13 27 Conversely, tools such as PROVEN 28 33 and Hello Project 34 38 used video and game-based approaches respectively, illustrating the variety of delivery methods. The web-based tool, Making Your Wishes Known, 39 43 offers wide accessibility, while PC-ACP 44 48 and SPIRIT 49 53 highlight the significance of individual counseling in ACP.…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing that ACP is achieved through a process of iterative conversations and that content changes over time, collecting measures longitudinally may provide a more complete picture of clinical activity than what cross-sectional measures allow. Longitudinal, patient-reported measures may be particularly useful in evaluating interventions to improve communication, such as the Serious Illness Care Program [ 37 ] or PREPARE For Your Care [ 38 ]. Future studies could explore the longitudinal congruency between patient-perceived rates of ACP discussion and rates of discussion as documented in their medical records, as well as the similarities and differences in what patients and their HCPs find meaningful to discuss and to document during clinical encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Closely related to chronic pain, it was found that this RCT, in which a planned HL intervention program was analyzed in comparison with an intervention directive between oncological and non-oncological patients, whose secondary outcomes were depression and/or anxiety and HL, among others. Ease of use of the documentation and satisfaction were high, and depression/anxiety was low, with no differences based on the study arm or whether the patient had cancer or not ( 107 ). In another geographical context and with the same objective, the prevalence of symptoms of depression and anxiety and mental health literacy (MHL) in outpatients with or without cancer was evaluated.…”
Section: Discussionmentioning
confidence: 99%